2021
DOI: 10.4236/ojoph.2021.112014
|View full text |Cite
|
Sign up to set email alerts
|

Obese Foveal Avascular Zone Assessed by Optical Coherence Tomography Angiography of the Retina: Is There a Relation to Comorbities?

Abstract: Purpose: To investigate the foveal avascular zone (FAZ) in obese by optical coherence tomography angiography (OCT-A) and to evaluate the findings of structural optical coherence tomography (OCT) and their relations with comorbidities. Methods: It was included 35 obese (study group) and 30 normal individuals (control group). Patients with retinal diseases and retinal treatments were excluded. The images were obtained using the Topcon ® . Results: The mean areas of FAZ in superficial plexus (FAZ-SP) and deep ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To date, very little research has been carried out, investigating the relationship between the foveal avascular zone area and overweight/obesity. One study, involving a smaller cohort (n = 35 obese, n = 30 control subjects), reported a significantly larger foveal avascular zone area in the superficial and deep plexus in obese subjects (>30 kg/m 2 ) 24 . Furthermore, a significant association between a larger foveal avascular zone area in the deep plexus and type 2 diabetes was observed 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, very little research has been carried out, investigating the relationship between the foveal avascular zone area and overweight/obesity. One study, involving a smaller cohort (n = 35 obese, n = 30 control subjects), reported a significantly larger foveal avascular zone area in the superficial and deep plexus in obese subjects (>30 kg/m 2 ) 24 . Furthermore, a significant association between a larger foveal avascular zone area in the deep plexus and type 2 diabetes was observed 24 .…”
Section: Discussionmentioning
confidence: 99%
“…One study, involving a smaller cohort (n = 35 obese, n = 30 control subjects), reported a significantly larger foveal avascular zone area in the superficial and deep plexus in obese subjects (>30 kg/m 2 ) 24 . Furthermore, a significant association between a larger foveal avascular zone area in the deep plexus and type 2 diabetes was observed 24 . Overweight/obesity is considered an important factor in the etiology of type 2 diabetes 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced vessel density and perfusion, lower CMT and high BMI/ trunk fat % are all associated with in ammatory conditions and with a larger FAZ area. [21], [52], [64], [66], [67] In ammation is associated with oxidative stress, which can cause retinal damage over time. Furthermore, in the current study, larger FAZ area was associated with lower MP status and, therefore, antioxidant status in a young, healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…However, one small study, (n = 65) found a larger FAZ area in obese subjects. [52] Obesity is associated with oxidative stress, which in turn; is linked with capillary dropout and damage to the retinal vasculature. [53] Overweight/obesity is also considered an important factor in the aetiology of Type 2 diabetes.…”
Section: Body Mass Index Waist To Height Ratio and Trunk Fat Percentagementioning
confidence: 99%